The Mind-Body Problem and Libertarian Freedom of the Will - Dagys, Jonas (Problemos, 2008)
The paper analyzes the relation between the mind body problem and the problem of free will within the physicalist framework. It is argued that the problem of free will, as far as metaphysics is concerned, is a specific case of the mind-body problem, namely the problem of how can mental events have physical effects. One need not be eliminativist to be a physicalist about the mind - reductionism or epiphenomenalism is perfectly compatible with the causal closure of the physical world, while preserving certain reality of the mental, but neither epiphenomenalist nor reductionist strategy can save libertarian freedom. If this is in fact so, then somewhat more general conclusion follows: physical determinism and fatalism do not exhaust the opposition to libertarians, and thus the falsity of the two would not in any case suffice to establish libertarian position as true.